Opportunities and Strategies for Accelerating Digital Transformation: Spatial Distribution Analysis and Clustering Using K-Medoids Method In South Sulawesi, Indonesia - Idris, Aditya; Susilawati, Sumarni (Journal of Mathematics and Applied Statistics, 2024)
The increase in internet usage among the population in South Sulawesi prsesents a golden opportunity for accelerating digital transformation efforts. This can be leveraged to boost economic growth, particularly by maximizing the key sectors in South Sulawesi. The aim of this study is to analyze the spatial distrubution and perform clustering of the regencies/cities in South Sulawesi based on digital transformation indivators, as well as to determine the multiplier effect on other regions in Sulampua. The research method employed is quantitative, utilizing descriptive analysis and clustering analysis of regencies/cities in South Sulawesi with the K-Medoids method. The results show that spatially, the distribution of internet users, e-commerce users and SMEs using the internet have quite varied patterns and reveal a high disparity in service users among regencies/cities in South Sulawesi. Meanwhile, the clustering results indicate that the regencies/cities in South Sulawesi are balanced between cluster 1 and cluster 2, each consisting of 12 regencies/cities. It was found that cluster 2, which includes regencies and cities in South Sulawesi, has better variable values in almost all variables comparated to the regencies/cities in cluster 1. Generally, cluster 2 dominates all the variables used, while cluster 1 is only superior in the variable of the number of SMEs. The suggestions and policy recommendations for the government based on this study on the acceleration of digital transformation with spatial distribution and clustering analysis can help create on environment that supports sustainable digital economic growth. With coordinated and collaborative policy strategies, South Sulawesi can achieve significant acceration in digital transformation.